Алгебраические многочлены, наименее уклоняющиеся от нуля по мере на отрезке - Арестов, В.В. (Український математичний журнал, 2010)
Досліджується задача про алгебраїчні многочлени із заданим старшим коефіцієнтом, що найменше відхиляються від нуля за мірою на відрізку [–1,1], а точніше, відносно функціонала μ(f)=mes{x∈[–1,1]:∣f(x)∣≥1}. Обговорюється аналогічна задача відносно інтегральних функціоналів ∫1–1φ(∣f(x)∣)dx для функцій φ, визначених, невід'ємних та неспадних на півосі [0,+∞). We investigate the problem of algebraic polynomials with given leading coefficients that deviate least from zero on the segment [–1, 1] with respect to a measure, or, more precisely, with respect to the functional μ(f) = mes{x ∈ [–1, 1]: ∣f (x)∣ ≥ 1}. We also discuss an analogous problem with respect to the integral functionals ∫ –11 φ (∣f (x)∣) dx for functions φ that are defined, nonnegative, and nondecreasing on the semiaxis [0, +∞).